CUSTOMER SATISFACTION SURVEY ON HALDIRAM - SMITHA KOTHARI (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Customer Satisfaction Survey on HALDIRAM is the working title for this endeavour. In order to gather information for this project, I've been exploring the company's online presence, reading blogs and visiting distributors and retailers. The sum of all chips and namkeens sold in supermarkets, convenience stores, specialty food stores, supermarkets, malls, big bazaars, and other retail establishments is included